2008
DOI: 10.2165/00002018-200831060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity Profile of Trastuzumab

Abstract: Trastuzumab is a monoclonal antibody that targets the human epidermal growth factor receptor tyrosine kinase HER2/ErbB2. This agent has shown a highly significant antitumour effect for patients with HER2-positive breast cancer, and is now considered part of the standard regimens for the treatment of this disease in both the metastatic and adjuvant setting. Cardiotoxicity has been associated with trastuzumab, and this issue has now been studied and documented in a number of adjuvant trials for which data have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 21 publications
1
109
1
8
Order By: Relevance
“…Wywiady HF, dysfunkcji serca, nadciśnienia tętniczego, cukrzycy lub CAD powodują, że układ CV jest bardziej wraż-liwy na dodatkowe obciążenia wynikające z chemioterapii lub napromienienia [218][219][220].…”
Section: Pacjenci W Podeszłym Wiekuunclassified
“…Wywiady HF, dysfunkcji serca, nadciśnienia tętniczego, cukrzycy lub CAD powodują, że układ CV jest bardziej wraż-liwy na dodatkowe obciążenia wynikające z chemioterapii lub napromienienia [218][219][220].…”
Section: Pacjenci W Podeszłym Wiekuunclassified
“…However, these drugs are potentially cardiotoxic and may induce heart damage leading to heart failure (HF). The likelihood of cardiac side effects during adjuvant chemotherapy is related to the type of therapy, schedule of administration, and other wellknown risk factors [2], including the timing of trastuzumab therapy [3]. It has been shown that the use of trastuzumab with standard chemotherapy (anthracycline and cyclophosphamide) significantly increases the risk of cardiac dysfunction in patients with epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…(75) Its use however has resulted in an unexpectedly high rate of cardiotoxicity which occurs in up to 7% of patients when used as monotherapy and in 28% of patients when associated with AC.…”
Section: Trastuzumab-induced Cardiotoxicitymentioning
confidence: 99%